Salt in his shoes : Michael Jordan in pursuit of a dream - Jordan, Roslyn; Jordan, Deloris; Nelson, Kadir (New York : Simon & Schuster Books for Young Readers, 2000)
Young Michael Jordan, who is smaller than the other players, learns that determination and hard work are more important than size when playing the game of basketball.
Keywords: Jordan, Michael, -- 1963- -- Childhood and youth -- Juvenile fiction; Jordan, Michael, -- 1963- -- Childhood and youth -- Fiction; Basketball -- Fiction; Size -- Fiction